Gerakan sosial petani : pola, strategi, dan tantangan di tengah modernitas / Ahmad Izudin; editor, Miftachul Huda - AHMAD IZUDIN , 1989-; Miftachul Huda (Samudra Biru, 2017)
x, 267 hlm. : ilus. ; 20 cm.